Navigating Polyvocal Heritage in a Postcolonial Cultural Landscape - van Donkersgoed, Joëlla (Taylor & Francis, 2026)
This book explores the complex histories and heritage of the Banda Islands in Indonesia. By interweaving oral traditions with colonial and archaeological records, it examines polyvocality in heritage interpretation and the central role of communities in shaping their cultural landscapes. The book provides a polyvocal approach to heritage studies, blending historical narratives, cultural landscape analysis, and postcolonial critique. It provides insights into the resilience of Bandanese traditions, the challenges of heritage management, and strategies for inclusive conservation. Through the case study of Fort Nassau on the Banda Islands, the book delivers a nuanced framework for understanding and preserving the complex polyvocal realities of postcolonial cultural landscapes. Navigating Polyvocal Heritage in a Postcolonial Cultural Landscape will be of value to researchers, and students in history, archaeology, heritage studies, area studies, and postcolonial studies. It is also relevant to heritage professionals, policymakers, and institutions involved in cultural heritage management and conservation, particularly those interested in working with community-based heritage approaches.